2017
DOI: 10.1016/j.astropartphys.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

γ-Ray polarimetry with conversions to e+e pairs: Polarization asymmetry and the way to measure it

Abstract: We revisit the measurement of the polarization fraction, P , and the measurement of the polarization angle of partially linearly-polarized gamma rays using their conversion to e + e − pairs in the field of a nucleus. We show that an inappropriate definition of the azimuthal angle, ϕ, used to reference the orientation of the final state degrades the precision of the measurement of P , by comparison to the optimal case where the bisector angle of the electron and of the positron momenta is used. We then focus on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…In the case of interest of a final state consisting of three particles (even when the recoil cannot be measured), the definition of the azimuthal angle, φ, is an issue. We determined the bisector φ +− = (φ + + φ − )/2 of the azimuthal angles of the direction of the electron, φ − , and of the positron, φ + , to be the optimal choice [27]. We demonstrated that with that angle definition, our generator is the only one, to our knowledge, to match the known asymptotic expressions for A at low and at high energies [24].…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…In the case of interest of a final state consisting of three particles (even when the recoil cannot be measured), the definition of the azimuthal angle, φ, is an issue. We determined the bisector φ +− = (φ + + φ − )/2 of the azimuthal angles of the direction of the electron, φ − , and of the positron, φ + , to be the optimal choice [27]. We demonstrated that with that angle definition, our generator is the only one, to our knowledge, to match the known asymptotic expressions for A at low and at high energies [24].…”
mentioning
confidence: 94%
“…We implemented the moments' method to obtain an optimal measurement of the polarisation modulation factor A × P . In the case of the simple 1D differential cross section, the method is equivalent to a maximum likelihood fit of the 1D differential cross section dσ/dφ ∝ (1 + A × P cos(2(φ − φ 0 ))) [11,27]. In the case of the full 5D differential cross section, an additional gain in the precision of the measurement of A × P of a factor of two-to-three is obtained [11,27].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This enabled us to access the geometry of the gamma-ray conversion, in particular, the azimuthal angle of the conversion plane of the event. It has been shown [13] that the precision of the measurement of the polarisation fraction depends on choosing optimally the angle that is measured and that the highest precision can be achieved if the bisector angle of the electron and of the positron momenta is used. The geometry of the conversion can be seen on the left of Figure 4.…”
Section: Pos(ifs2017)180mentioning
confidence: 99%
“…MeV polarimetry using a TPC Deirdre Horan Figure 3: Examples of events recorded in the HARPO detector from [13]. From left to right are plotted events corresponding to a Compton scattering, a pair conversion and a triplet conversion.…”
Section: Pos(ifs2017)180mentioning
confidence: 99%